Irradiation before and donor splenocyte infusion immediately after transplantation induce tolerance to lung, but not heart allografts in miniature swine. (5th March 2017) - Sommer, Wiebke; Buechler, Gwen; Jansson, Katharina; Avsar, Murat; Knöfel, Ann‐Kathrin; Salman, Jawad; Hoeffler, Klaus; Siemeni, Thierry; Gottlieb, Jens; Karstens, Johann H.; Jonigk, Danny; Reising, Ansgar; et al.
Summary: Solid organs may differ in their potential to induce and maintain a state of donor‐specific tolerance. Previously, we induced stable immunological tolerance in a lung transplantation model in miniature swine. Here, we wished to transfer this established protocol into a heart transplantation model in miniature swine. Heterotopic heart transplantation (HTX) was performed in four and left‐sided lung transplantation (LTX) in seven minipigs from gender‐ and SLA‐mismatched donors. All recipients received nonmyeloablative irradiation, donor splenocyte infusion and intravenous pharmacologic immunosuppression for 28 postoperative days. All transplanted hearts were rejected within 95 days. In contrast, four animals of the LTX group developed stable tolerance surviving beyond 500 days, and three further animals rejected 119, 239 and 360 days post‐transplantation. In both groups, peripheral blood donor leucocyte chimerism peaked 1 h after reperfusion of the allograft. Importantly, the early chimerism level in the LTX group was significantly higher compared to the HTX group and remained detectable throughout the entire observation period. In conclusion, lungs and hearts vary in their potential to induce a state of tolerance after transplantation in a protocol with pre‐operative recipient irradiation and donor splenocyte co‐transplantation. This could be due to differential early levels of passenger leucocyte chimerism.